HERMENEUTICS IN THE INTERPRETATI HERMENEUTICS IN THE INTERPRETATION OF QUR’AN: HERMENEUTIKA DI DALAM TAFSIR AL-QUR'AN - MUHAMMAD FAUZI NOOR (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2024)
Hermeneutics, as a new method of interpreting the Qur'an, is expected to be able to reveal things that cannot be known with other forms of interpretation. The author strives for this research to examine various hermeneutical method approaches in Islamic studies. The technique used in this research is a literature study. The results obtained from this research are that hermeneutics can be interpreted as an interpretation method that pays attention to the context of the words of a text and the cultural context of thought. Hermeneutics is considered to have a distinctive characteristic, namely the development of contextualization values of a text to be studied. Hermeneutics in the Islamic study of the interpretation of the Al-Qur'an finds the correspondence between the verses of the Al Qur'an in science. Also, it shows the miracles of the Al-Qur'an and its glory.